Design and Fabrication of Aluminium/Alumina Ultra-fine Composite and Functionally Graded Material Using Powder Metallurgy Route - Tripathy A.; Gupta R.; Sarangi S.K.; Chaubey A.K. (My University, 2025)
Composites with light metals as the matrix and ceramic particles as the reinforcements are being acknowledged widely during the past decade for their superior mechanical properties, the most successful among them have been Aluminium/Alumina (Al/Al2O3) composite where Alumina particulates are reinforced in Aluminium matrix. Present work deals with fabrication and characterization of Al/Al2O3 ultra-fine composites with 10, 20, 30 and 40% Al2O3. These ultrafine composites are fabricated using uniaxial hot press under 10−5mbar vacuum pressure at 400 °C sintering temperature and 3-tonne load for 2 h experimental condition. Effect of Al2O3 volume fraction on microstructural and mechanical properties of the composite are studied through optical microscopy. Phase analysis and microstructure investigations revealed that the consolidated material consists of Al as a matrix phase and Al2O3 phases with size below 1 µm homogeneously dispersed in a continuous matrix. Taking into consideration the results of above experiment, Al/Al2O3 system Functionally Graded (FG) Material is successfully hot pressed using powder metallurgy (PM) route under similar experimental conditions. It is found that relative density of the Al/Al2O3 FG Material increased with the rise in sintering temperature and its density range changed quasi-continuously from 2.67 × 103 kg/m3 to 2.71 × 103 kg/m3, while the microhardness value obtained at the top surface was 35.2 HV which gradually increased across its thickness to 74.81 HV at the other surface with the increase in reinforced Al2O3. This FGM is intended to be a good substitute ‘low weight high strength material’ with better wear resistance properties at elevated temperatures. © 2020, Springer Nature Singapore Pte Ltd.